Dog Man. For whom the ball rolls - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York : Graphix, 2019)
Dog Man has been working hard to overcome his bad habits, but when his obsessions turn to fears, he finds himself the target of an all-new supervillain, while Petey the Cat, who was just released from jail, starts a new life with Li'l Petey.
2.5
3-6
GN550L
Keywords: Police -- Comic books, strips, etc. -- Fiction; Dogs -- Comic books, strips, etc. -- Fiction; Cats -- Comic books, strips, etc. -- Fiction; Heroes -- Comic books, strips, etc. -- Fiction; Police -- Fiction; Dogs -- Fiction; Cats -- Fiction; Heroes -- Fiction; Cartoons and comics; Humorous comics; Graphic novels